High Genetic Diversity of Porcine Sapovirus From Diarrheic Piglets in Yunnan Province, China - Liu, Xiao; Song, Chunlian; Liu, Yinghua; Qu, Kaixing; Bi, Junyu; Bi, Junlong; Wang, Yunhua; Yang, Ying; Sun, Junhua; Guo, Zhigang; Li, Ganwu; Liu, Jianping; et al. (Frontiers in Veterinary Science, 2022)
As one of the most important enteric viruses, Sapovirus (SaV) can infect humans and a variety of animals. Until now, 19 SaV genogroups have been identified, among which 4 from human (GI, GII, GIV and GV) and 8 from swine (GIII, GV–GXI). Porcine sapovirus (PoSaV) GIII has been prevalent in China, however, the status of PoSaV infection in Yunnan province remains unknown. In this study, 202 fecal samples were collected from diarrheic piglets in Yunnan between January and May of 2020. PoSaV detection revealed that the total PoSaV infection rate in Yunnan was 35.2%, with 21 PoSaV strains determined and phylogenetically analyzed. The phylogenetic tree analyses demonstrated that twenty PoSaV strains belonged to GIII and fell into five genotypes, while one PoSaV strain (YNQB) belonged to GV. Sequence alignments revealed deletions inVP2 region in 10 of the 20 GIII strains, as well as deletions and insertions in VP1 region of the GV strain (YNQB). Furthermore, genomic recombination analyses showed that two GIII strains (YNAN and YNJD) were recombinants, closely related to reference sequences MK965898 and LC215880, MK965898 and FJ387164, respectively. In summary, PoSaV-GIII strains were prevalent in Yunnan in 2020 and for the first time a PoSaV-GV strain was identified from China, while the comprehensive analyses illustrated high genetic diversity of Yunnan PoSaV strains. This study may shed new light on the current PoSaV infections in Yunnan and pave the way towards further control of the PoSaV infections in China.